TINJAUAN PERENCANAAN MANAJEMEN KONSTRUKSI PADA PEMBANGUNAN GEDUNG REHABILITASI NAPZA KOTA PONTIANAK: TINJAUAN PERENCANAAN MANAJEMEN KONSTRUKSI PADA PEMBANGUNAN GEDUNG REHABILITASI NAPZA KOTA PONTIANAK - Febriski Fajar, Andini; Febrina, sarah (Jurusan Teknik Sipil Polnep, 2023)
When carrying out a construction project activity, a construction management system is needed. ConstructionManagement includes management of project cost control (RAB), time (Schedule), human resources (HR),project occupational health safety management (SMK3L) and risk classification and control. Projectimplementation control must be carried out from the beginning of the work until the project work is completedso that construction management must be by the implementation. The results of the review of constructionmanagement planning for the construction of the NAPZA building were dominant in the implementation phase,especially in time control where the project construction process which was originally planned for 148 daysor approximately 22 weeks became 24 weeks. This resulted in the problem of processing time where the targetwas not achieved and resulted in delayed project work. Project implementation control must be carried outfrom the start of work until the project is declared complete so that during the project development processunwanted problems can be avoided. The construction management that will be applied to the NAPZA buildingcan make the project run well and according to the desired schedule.